Effectiveness of behavioral ivan pavlov conselvation the using modeling techniques to increase characters to completely complete duties through leason study - Sulatri, Desak Kadek; Dharsana, I Ketut; Suarni, Ni Ketut (Konselor, 2019)
This study aims to determine the effectiveness of behavioral counseling Ivan Pavlov with modeling techniques to improve the character of completing tasks well through lesson study on students first grade. This type of research is quasi-experimental with pre-test and post-test control group design. The sample is 34 students with df 33. The method of collecting data uses a character questionnaire to complete tasks well as many as 30 items. The results of data analysis are t value tcount 26.60> ttable 2.03 so Ho is rejected and Ha is accepted. So there are significant differences. It can be concluded that Ivan Pavlov's behavioral counseling is an effective modeling technique for improving character completing tasks well.